Treatment of refractory ulcers of the rectum by autologous stem-cell transplantation - S. F. Bagnenko; V. P. Morozov; A. S. Nemkov; A. A. Kamanin; A. Yu. Korolkov; O. B. Shchukina; A. A. Vinichenko (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to improve the quality of diagnosis and the effectiveness of treatment of refractory ulcers of the rectum. METHODS AND MATERIALS. We analyzed clinical and biochemical parameters in 39 patients with previously diagnosed solitary ulcers of the rectum. It was proved that in 18 patients, ulceration in the rectum was caused by an autoimmune process, according to the type of Crohn’s disease. The obtained data made it possible to substantiate and apply a new method of treating rectal ulcers – local bone marrow stem cell transplantation. RESULTS. All patients had pain, stool returned to normal, and ulcerative defects were noted to heal. CONCLUSION. Bone marrow stem cell transplantation differs fundamentally in its mechanism of action from known methods of treating rectal ulcers. The method has shown high efficiency and a good safety profile.